Prospek Karir Lulusan Sekolah Menengah Kejuruan: Content Audit terhadap Kurikulum dan Tema Layanan Konseling - IM Hambali (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
This study aims to describe: (1) prior and retrospective knowledge, (2) untrained skills, and (3) attitude to be induced as the knowledge, skills, and attitude to support students’ future career. This study used descriptive design and data were analyzed using descriptive statistics. Results show that practices on career development for vocational schools indicate that (1) the knowledge on capitalization, persuading potential customers, and product efficiency are trained shortly to students, (2) skills to optimalize online media, capitals, banking, and networking for cooperation are not yer trained by the local schools, and (3) few schools provide pieces of training on the benefits of product marketing as the future prospect.